Studi Komparatif Tentang Nikah Syighar - Fauhan Thirafi; Muhammad Rizki Firmansyah (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
This research aims to conduct a comparative study of syighar marriage from the perspective of Islamic schools of thought, as well as reviewing its relevance in the context of modern marriage law. This writing uses literature research or library study methods, with the process of collecting, analyzing, interpreting data and conclusions from various books related to the problem discussed. According to Imam Hanafi, this marriage is still considered valid, whereas according to Jumhur this marriage is invalid and annulled.